Case report - pre-transplant testing and post-transplant monitoring for an HLA-immunized recipient in heart transplantation - Jukić, Lucija, molekularna biologinja (Array, 2020)
We report the workflow of immunogenetic pre-transplant testing and post-transplant monitoring in the case of a recipient immunized to human leucocyte antigens (HLA) who was waitlisted for heart transplantation. The recipient underwent heart transplantation across preformed HLA class I Donor Specific Antibodies (DSAs) detected by solid phase Luminex screening method but not by complement dependent cytotoxicity (CDC) screening method. The CDC lymphocyte crossmatch, which was performed retrospectively, was a weak positive. Post-transplant DSA monitoring by Luminex method revealed the decrease of HLA-A1, A25 and B57 DSAs with, at the same time, an increase of HLA-B8 DSA, as well as weak transient non-DSA HLA-DP antibodies. This case presents the importance of extensive immunogenetic testing and monitoring for identifying recipients with increased immunological risk for successful heart transplantation.